1983
DOI: 10.1128/iai.40.3.1170-1177.1983
|View full text |Cite
|
Sign up to set email alerts
|

Course of infection and development of immunity in experimental infection of mice with Listeria serotypes

Abstract: NMRI mice were experimentally infected with Listeria monocytogenes serotypes 1/2b, 3a, 4b, and 4d and Listeria innocua serotype 6b by different means. The course of infection was monitored, using bacteriological and histological nocua were used. L. monocytogenes: serotype 1/2b, SLCC 2755; serotype 3a, SLCC 2373 = NCTC 5105 = ATCC 19113; serotype 4b, two strains originally isolated from human clinical material (cerebrospinal fluid 1170 on July 16, 2020 by guest http://iai.asm.org/ Downloaded from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Numerous previous studies on the experimental infection of mice by L. monocytogenes strains have remarked on the occurrence of weakly virulent strains isolated from food and clinical samples, but the basis of the lowered virulence has not been systemically examined [14,15,20,21]. Here we show that, despite their intermediate level of virulence, primary infection with such naturally occurring strains afford protection to subsequent infection by more pathogenic variants.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Numerous previous studies on the experimental infection of mice by L. monocytogenes strains have remarked on the occurrence of weakly virulent strains isolated from food and clinical samples, but the basis of the lowered virulence has not been systemically examined [14,15,20,21]. Here we show that, despite their intermediate level of virulence, primary infection with such naturally occurring strains afford protection to subsequent infection by more pathogenic variants.…”
Section: Discussionmentioning
confidence: 58%
“…The question arises as to what these protective antigens might be. Numer-ous immunization studies performed previously with non-pathogenic Listeria have demonstrated their inability to generate long-lasting protection [13][14][15]. Also, mice infected with listeriolysinnegative strains do not acquire resistance because such bacteria are rapidly eliminated from the infected host even if repeated doses at regular intervals were administered to mice [16].…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of the L. monocytogenes strains in the livers and spleens and the histopathology of these tissues reflected the typical course of listeric infection and development of a cellular immune response by 3 to 4 days postinoculation (1,8,20,26,28,52). The larger populations of SA in the livers than in the spleens are characteristic of listeriosis in pregnant mice (32), whereas in nonpregnant mice larger populations of L. monocytogenes are consistently recovered from the spleen (2,20,32).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, L. innocua is recovered from the livers and spleens of mice inoculated by i.p. and intravenous injection but is rapidly eliminated without evoking an immune response (20,52).…”
Section: Discussionmentioning
confidence: 99%
“…These virulent Listeria strains are able to replicate within professional phagocytes, as demonstrated during in vitro and in vivo studies (10,13). In contrast, exposure to either apathogenic Listeria strains or nonviable virulent L. monocytogenes fails to promote a protective immune response (1,3,6,7,12,22,23) unless associated with an adjuvant (19)(20)(21). Furthermore, antigen preparations derived from listerias fail to induce acquired resistance as well.…”
mentioning
confidence: 99%